(untitled) (Innovative professional education, 2024)
The essence of the concept of «pedagogical condition» is revealed. The main pedagogical conditions for the formation of professional competence of future economists are defined and characterized: ensuring positive motivation to master the future specialty; use of active learning methods; mastering the practical experience of future professional activity; information provision of the educational process of training future specialists for professional activity; activation of scientific research work of students and teachers.